(untitled) (MAUSAM, 1970)
Procedural steps involved in the estimation of design storm rainfall for a hilly catchment with inadequate raingauge network has been discussed and applied for evaluation of Standard Project Storm and Maximum Probable Storm for the Barak basin (upto Silchar), located in south Assam. Attempt has been made to correlate normal monsoon seasonal rainfall on the windward and lee sides to the elevation of the hills surrounding the catchment. Utilising these relationships normal seasonal rainfall for the ungauged stations situated inside the basin has been more number 0£ estimated and the normal seasonal isohyetal pattern evolved for the basin. Isopercental technique has been used for ears are studied assessing isohyetal pattern for the major flood. Producing rainstorms and their weighted rainfall depths obtained for tended to obtained the basin and maximised for the moisture charge.